Is guideline-driven prophylaxis for venous thromboembolism common practice in the South African private hospital setting? - Melissa van der Merwe; Marlene Julyan; Jesslee M. du Plessis (South African Family Practice)
Background: Prophylactic venous thromboembolism (VTE) strategies have the greatest impact on patient outcomes. Both global and local guidelines support VTE prophylaxis for hospitalised patients. However, studies have reported that these measures are routinely under-prescribed. This study evaluated prescribing patterns of VTE prophylaxis in one of the largest South African (SA) private hospital groups.